Edukasi pada Ibu Hamil dan Menyusui tentang Pentingnya Vaksinasi Lengkap (Dosis 1 dan 2) Covid-19 di Kabupaten Buton Selatan - Dahniar Dahlan; Wa Ode Nesya Jeni Samrida; Wa Ode Nurul Mutia; Yohanis Rongre; Anarisa; Anita Anita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2022)
Vaccination is one of the efforts to overcome covid-19 to reduce morbidity and mortality due to covid-19. The implementation of the covid-19 vaccination for pregnant women and breastfeeding mothers has received many pros and cons in the community, especially people in remote areas. So many people refuse to get vaccinated against covid-19. The increase in cases of exposure to covid-19 in pregnant women and breastfeeding mothers was found in urban areas and even in remote areas, especially in Bola Village, South Buton Regency. Based on this case, we conducted education to pregnant women and breastfeeding mothers by distributing questionnaires. This was followed by a discussion and question and answer session about the importance of the covid-19 vaccination. We hold counseling for pregnant women and breastfeeding mothers so that they can understand and participate in government programs by carrying out complete vaccinations (dose 1 and 2) in order to break the chain of spread of covid-19. It is known that there is an increase in knowledge of pregnant and lactating mothers about covid-19 vaccination before and after participating in health counseling in the form of lectures and joint discussions.